An Attempt to Understand the Driving Forces of Historiography in the Eurocentric Perspective in Southeast Asia - Mehmet Özay (İnsan & Toplum)
In this paper, I will sketch the issue of historical writing in the Eurocentric perspective concerning two regions, Malaya and the East Indies in Southeast Asia. The reason to take these re- gions into consideration in the same text can be justified on the basis that both regions have been historically and anthropologically considered concentric. With regard to this region, this paper is an overall attempt to understand the successive efforts of Western individuals writing history from the Eurocentric perspective since the earlier period of Western intervention in the regional socio-economic and cultural changes. In fact, absorption of the native histories is not just a reflec- tion of understanding the native, but an attempt to transform them for some supposedly higher ideals. In this context, it would be neglectful if we did not also note that the native communities in the Eastern sphere of the Indian Ocean studied in this text have historically had Muslim majorities.